Incidence of Superficial and Deep Surgical Site Infections in Post Cardiac Surgery Patients with Pre-Operative HBA1C ≥ 7 % Compared to Those Having Pre-Operative HBAIC < 7% - Tufail Ahmad, Sobia Siddique, Abubakar Sadiq (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The main objective of the study is to find the Incidence of superficial and deep surgical site infections in post cardiac surgery patients with pre-op HBA1C ≥ 7 % compared to those having pre-op HBAIC < 7%. Material and methods: This cross-sectional study was conducted in Armed forces institute of cardiology AFIC /NIHD Rawalpindi during 1st October 2022 to 30 November 2022. Data was collected with the permission of ethical committee of hospital. All the patients who met the inclusion and exclusion criteria were selected for the study. As a routine practice at the cardiac surgery outpatient clinic of our hospital, HbA1c levels of diabetic patients are examined along with other routine examinations approximately 7–10 days before the surgery. Results: The data was collected from 354 patients of age range was 58.98 ± 4.56 years. According to analysis that was performed to investigate the mortality predictivity, age, gender, input ejection fraction, HbA1c levels and preoperative albumin levels were found to be associated with mortality. In the group with HbA1c≥7, the ejection fraction was lower (p=0.027) and mortality was higher (p=0.008). Practical Implications: Increased level of HbA1c>7 in cardiac surgery patients is considered to be the increased incidence of SSI. Conclusion: Increased level of HbA1c>7 in cardiac surgery is considered to be the increased incidence of SSI. We also found that good peri-operative control of RBS associated with decreased rate of SSI after cardiac surgery. Keywords: Cardiac, HbA1c, Diabetic, Surgery, Ejection fraction